2019
DOI: 10.1371/journal.pone.0224170
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of community acquired pneumonia management strategies: A systematic review of literature

Abstract: BackgroundCommunity-acquired pneumonia (CAP) is a major cause of mortality and morbidity worldwide. Efficient use of resources is fundamental for best use of money among the available and novel treatment options for the management of pneumonia. The objective of this study was to systematically review the economic analysis of management strategies of pneumonia.MethodsA systematic search was performed using Academic Search Complete, MEDLINE, EconLit, Global health, MEDLINE complete and Embase databases using spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
(130 reference statements)
1
6
0
Order By: Relevance
“…LoS in hospital was the most important cost predictor and the most sensitive cost parameter in our study, which is consistent with recent reviews on pneumonia management 9 10. Per-patient provider cost varied across referral cases, with no cost variation in relation to other clinical variables such as age, sex and presence of hypoxaemia.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…LoS in hospital was the most important cost predictor and the most sensitive cost parameter in our study, which is consistent with recent reviews on pneumonia management 9 10. Per-patient provider cost varied across referral cases, with no cost variation in relation to other clinical variables such as age, sex and presence of hypoxaemia.…”
Section: Discussionsupporting
confidence: 90%
“…Major strengths include the application of a micro-costing bottom-up approach using patient-level data to estimate cost per patient, informed by literature reviews 9 10. The analysis included a large sample and estimated detailed cost for each included facility covering urban and rural areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CHEERS checklist contains a total of 28 items on six categories: (1) title, (2) abstract, (3) methods, (4) results, (5) discussion, and (6) other relevant information. The following grading method, used for the quality assessment in the previous systematic reviews [ 21 , 22 ], was adopted in the present assessment: 1 point was granted to each CHEERS item when the item-specific requirements were fully complete, 0.5 point for partially satisfied, and 0 point for not satisfied. Each included study was then categorized into 1 of 4 completeness categories: excellent (scored ≥85%), very good (scored between 70% and 84%), good (scored between 55% and 69%), and insufficient (scored <55%) [ 21 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…A study in rural Bangladesh has reported a positive association between the temperature and humidity and the length of stay (LoS) of children hospitalized for severe pneumonia [14]. The duration of the hospital stay is usually indicative of the severity of disease [15], and its rise causes a significant economic burden in both developed and developing countries [16]. The peak of daily temperature, humidity, and rainfall increases the risk of childhood pneumonia [2,10].…”
Section: Introductionmentioning
confidence: 99%